1996
DOI: 10.1212/wnl.47.2.583
|View full text |Cite
|
Sign up to set email alerts
|

Idebenone improves cerebral mitochondrial oxidative metabolism in a patient with MELAS

Abstract: We report a 36-year-old man with MELAS in whom a 5-month course of high-dose oral idebenone, a derivative of coenzyme Q10, increased markedly cerebral metabolic ratio of oxygen and oxygen extraction fraction without increased cerebral blood flow with PET. The results indicate that idebenone improves mitochondrial oxidative metabolism in the brain and suggest a therapeutic potential of idebenone for MELAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(28 citation statements)
references
References 2 publications
0
28
0
Order By: Relevance
“…To demonstrate this effect, previous studies used quinone concentrations, which were much higher than concentrations that can safely be achieved in vivo (high µM range) [8], [22]. Here, we describe for the first time that this mechanism can be observed in vitro at physiological concentrations, even in the low nanomolar range, which makes short-chain quinones an attractive option for the treatment of disorders associated with impaired mitochondrial complex I such as mitochondrial encephalopathy, lactic acidosis and stroke-like episodes (MELAS) [16], [17] and Leber's hereditary optic neuropathy (LHON) [18], [19]. Although NQO1-dependent electron shuttling from the cytoplasm to the mitochondria by quinones has been described previously [6], [21], [22], it was unclear whether these reports could be seen as individual observations that are exclusively linked to certain cellular model systems.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…To demonstrate this effect, previous studies used quinone concentrations, which were much higher than concentrations that can safely be achieved in vivo (high µM range) [8], [22]. Here, we describe for the first time that this mechanism can be observed in vitro at physiological concentrations, even in the low nanomolar range, which makes short-chain quinones an attractive option for the treatment of disorders associated with impaired mitochondrial complex I such as mitochondrial encephalopathy, lactic acidosis and stroke-like episodes (MELAS) [16], [17] and Leber's hereditary optic neuropathy (LHON) [18], [19]. Although NQO1-dependent electron shuttling from the cytoplasm to the mitochondria by quinones has been described previously [6], [21], [22], it was unclear whether these reports could be seen as individual observations that are exclusively linked to certain cellular model systems.…”
Section: Discussionmentioning
confidence: 86%
“…Successful treatment of a patient with Leigh syndrome using idebenone, where high-dose CoQ 10 had no effect on respiratory function, is indicative of therapeutic levels of idebenone in the brain [15]. Thus, idebenone has been suggested for treating patients with mitochondrial diseases, such as mitochondrial encephalopathy, lactic acidosis and stroke-like episodes (MELAS) [16], [17] and Leber's hereditary optic neuropathy (LHON) [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that idebenone is effective in improving the cardiac deficiency and cerebellar symptoms in patients with Friedreich's ataxia [12], which gene product is localized in the mitochondria. Idebenone has been given to three patients with MELAs [13][14][15] and reported to improve their clinical symptoms and cerebral functions, including electroencephalogram (EEG), IQ, and cerebral metabolic ratio of oxygen. However, its use in Leigh syndrome has not been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…This compound was originally developed with a view to treating dementia but has been reported in numerous cases of MELAS 35. It functions as a free-radical scavenger and bypasses complex I.…”
Section: Treatmentsmentioning
confidence: 99%